Some Characterizations of Left Weakly Regular Ordered Semigroups (Communications in Mathematical Research, 2021)
In this paper, the notion of left weakly regular ordered semigroups isintroduced. Furthermore, left weakly regular ordered semigroups are characterizedby the properties of their left ideals, right ideals and (generalized) bi-ideals, and alsoby the properties of their fuzzy left ideals, fuzzy right ideals and fuzzy (generalized)bi-ideals.